Electrochemical energy storage in a sustainable modern society - Goodenough, John B (Energy & environmental science, 2014)
The storage of electrical energy in a rechargeable battery is subject to the limitations of reversible chemical reactions in an electrochemical cell. The limiting constraints on the design of a rechargeable battery also depend on the application of the battery. Of particular interest for a sustainable modern society are (1) powering electric vehicles that can compete with cars powered by the internal combustion engine and (2) stationary storage of electrical energy from renewable energy sources that can compete with energy stored in fossil fuels. Existing design strategies for the rechargeable battery have enabled the wireless revolution and the plug-in hybrid electric car, but they show little promise of providing safe, adequate capacity with an acceptable shelf and cycle life to compete in cost and convenience with the chemical energy stored in fossil fuels. Electric vehicles that are charged overnight (plug-in vehicles) offer a distributed energy storage, but larger battery packs are needed for stationary storage of electrical energy generated from wind or solar farms and for stand-by power. This paper outlines the limitations of existing commercial strategies and some developing strategies that may overcome these limitations. Oxide/polymer separator membranes allow alternative strategies for Li-ion and Na-ion batteries storing electrical energy for the grid.